Respostas

2013-10-09T12:07:01-03:00
∆=(-12)²-4.9.(m+3)
∆=144-36m-108
∆=-36m+36

-36m+36>0
-36m>-36
36m>36
m>36
36
m>1
  • Usuário do Brainly
2013-10-09T12:13:46-03:00
(m + 3) = 0
m = - 3

logo:
9x'' - 12x + (-3) = 0
9x'' - 12x - 3 = 0
delta =  b^{2} - 4.a.c
delta = (-12)'' - 4.9.(-3)
delta = 144 + 108
delta = 252

mmc de 252
252/2
126/2
63/3
21/3
7/7

raiz delta = (2*2*3*3*7) = 2'' . 3'' . 7 = 6raiz7


x = - b +_ raiz delta / 2.a
x = - (-12) +_ 6 \sqrt{7} / 18
x = 12 +_ 6 \sqrt{7}  / 18 (simplifica por 6).
x* = 2 -  \sqrt{7}  / 3
x** = 2 +  \sqrt{7}  / 3
1 5 1